EFEKTIFITAS PENGOLAHAN LIMBAH CAIR DENGAN AERASI DALAM MENURUNKAN KADAR COD PADA LIMBAH BIODIESEL - Maris Anindita Fauzi; Setyani Hardiana Sunardi; Indro Sumantri (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Disposal of wastewater into bodies of water with a high content of COD load can cause a decline in the amount of oxygen in the water. Biodiesel manufacturing process wastewater to be discharged into the environment contains high COD, ie 1200 ppm. Processing carried out aerobically with COD values ​​of less than 1500 ppm to shorten the processing time. In addition, microbial & nutrients can be used to streamline the processing of waste in aerobic waste so that the output can meet environmental quality standards and certainly within a relatively short time. In this study degrasimba added bacteria and micro nutrients to the removal of COD in waste biodesel. Variable fixed in these experiments were MLSS 3000 mg / l, pH 7, the bacteria and micro nutrients that are used, the volume of waste, and waste type. Independent variable in this experiment is hidarulic retention time (HRT) with variations (8,12,14,dan16hours.). The results showed that the longer Hidarulic Retention Time (HRT), the higher removal of COD in the effluent. From the experimental results obtained COD with the longest HRT showed a decrease of 77.92% with a decrease from 1200 ppm to 265 ppm, and for HRT 8,12,14 hours respectively were 70.75%, 71.75% and & 72 , 83%. COD value obtained is 351.339, and 326 ppm in HRT each - respectively 8, 12, and 14 hours. With the COD levels of the average - average has decreased constantly on days 3 and 4..